(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The European Marine Energy Centre (EMEC) is the largest marine testing centre for marine energy technologies worldwide, and it is now working with tidal developers to test full-scale turbine arrays in 2026. To deliver this EMEC is expanding its existing infrastructure from a 12MW site to 50MW supported by significant private and public funding. One of the primary challenges related to Tidal Stream Turbine (TST) array development is the wake dispersion created by the first-row devices, which adversely affects the power output of neighbouring and downstream turbines, ultimately impacting the levelised cost of energy of the technology. While turbines are typically positioned at least 5-10 diameters behind the first rotor to mitigate this issue (based on learnings from the wind industry), downstream turbines still operate within the wake effects of the initial row, compromising their power generation and, in some cases, leading to structural damages due to the turbulent environment they endure. This turbulent environment can be further influenced by variations in bathymetry in a marine environment, altering flow patterns and giving rise to vortex formations detrimental to turbine rotors, reducing their operational lifespan. Expanding EMEC site could mean that the deployment of new turbines are exposed to more extreme environments that have not been accounted in the current designs and/or may pose a shorter life given the number of cycles that the turbines will need to withstand. As a first attempt to understand the new site requirement, this research thus aims to understanding the characteristics of the new site using a combination of field observations, in-situ measurements, and numerical modelling. The most accurate data is often obtained from instruments Acoustic Doppler Current Profilers (ADCPs), which are also expensive to install however, for which EMEC has some data available. Along this ADCP information, this work aims to assess the accuracy and performance of the data assimilation model, Finite Element Solution (FES), as initially done in [1], to assess the expansion site identified by EMEC. This will also include metrics to assess wave and wind directionality influences that may be larger depending on the new test sites explored. The results of this work will provide the required analysis to select the ideal sites to install the devices without compromising their operation. References [1] Bolivar-Carbonell, M, Lewis, M, Johnstone, C, Ordonez-Sanchez, S. (2024) Assessment of the FES2014c model for tidal currents on the shelves around the North Atlantic Ocean. Extended abstract accepted to be presented at the Pan-American Marine Energy Conference (PAMEC 2024), Barranquilla, January 2024.